The Effect of the Star Sportsmanship Education Module on Parents' Self-Perceived Sportsmanship Behaviors in Youth Sport - Dwedor W. Ford; Colby B. Jubenville; Michael B. Phillips (Journal of Applied Sports Management, 2013)
The purpose of this study was to examine how the STAR Sportsmanship education module affected parent behavior attached to their experience of their child’s sporting endeavors. The Parent Experiences in Youth Sport (PEYS) was utilized to collect data on 95 parents’ self-perceived behavior in youth sport. The PEYS consisted of an 18-item survey focused on how each participant rated their behavior as he/she experienced their child’s participation in some type of youth sport activity. Psychometric testing (e.g. content validity, known-group validity, test-retest reliability, and internal consistency) was conducted on the PEYS to provide validity and reliability evidence. The results indicated that 1) the PEYS is a reliable and valid survey for the assessment of parent sportsmanship behavior in youth sport and 2) the STAR Sportsmanship education module was an effective tool in teaching sportsmanship concepts to parents.
Keywords: STAR Sportsmanship Education Module; Sportsmanship; Youth Sports; Parent Experiences in Youth Sport; self-perceived sportsmanship behavior